2012
DOI: 10.1100/2012/601840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Soap of Fatty Acids Supplementation on Serum Biochemical Parameters and Ovarian Activity during Out-of-the-Breeding Season in Crossbred Ewes

Abstract: This experiment aimed to evaluate the effect of calcium soap of fatty acid (CSFA) supplementation on serum biochemical and hormones and ovarian activity during out-of-the-breeding season in ewes. Twelve crossbred ewes, 2-3 years of age and weighting 45–55 kg, were allocated into two equal groups. The first group was control and the other was treated with 50 g/head of CSFA. All ewes were fed basal diet and treated with 60 mg of medroxy progesterone acetate intravaginal sponge for 12 day. At the third day of spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Results of the research showed that the supplementation of 5% SOCS and 10% CFF in R2 and R3 rations did not give significant effect on the levels of cholesterol, triglycerides, LDL and HDL of Bali cattle. This result is different from the report of El-Nour et al (2012) who stated that the effects of fat supplementation in ewes feed resulted in the increased plasma concentrations of cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and progesterone.…”
Section: Blood Metabolitecontrasting
confidence: 98%
“…Results of the research showed that the supplementation of 5% SOCS and 10% CFF in R2 and R3 rations did not give significant effect on the levels of cholesterol, triglycerides, LDL and HDL of Bali cattle. This result is different from the report of El-Nour et al (2012) who stated that the effects of fat supplementation in ewes feed resulted in the increased plasma concentrations of cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and progesterone.…”
Section: Blood Metabolitecontrasting
confidence: 98%
“…Diet enriched with long chain n-3 PUFA resulted high ova release (Trujilo et al, 1995). El-Nour et al (2012) stated that PUFA from calcium soap of fatty acid supplementation increased ovulation rate, follicle number and the pregnancy rate. Vit E could prevent negative effect of noise on the pregnancy rate and the rate of fetal death and abortion on female mice (Fathollahi et al, 2013).…”
Section: Parameters Treatmentmentioning
confidence: 99%